The role of children's libraries in developing a multicultural dialogue - Reusch, Jutta (Knjižnica, 2009)
Internationale Jugendbibliothek München - International Youth Library in Munich has been collecting books for children and youth in all languages sinceits foundation in 1949 and it is the biggest library of this kind in the world. The intercultural dialogue encourages a number of different activities: lending children's and youth literature in 14 different languages, early literacy programmes for pre-school children in nationally mixed groups and programmes for school children and youth, English language courses, wide programme of exhibitions and scholarships for authors and publishers of children's and youth literature as well as for educators. The library publishers the annual catalogue "The White Ravens", bringing the selection of the best children's and youth literature in the world. It has turned out to be a reference tool for all dealing with literature for these two age groups.
Keywords: Internationale Jugendbibliothek München; splošne knjižnice; mladinski oddelki; knjižnične zbirke